The Effect of Optimism and Gratitude on Subjective Well-Being of Parents of Children with Special Needs - Musri, Amalia; Izzaty, Rita Eka; Gamil, Arwa (International Journal of Islamic Educational Psychology, 2024)
The children who are born with imperfect conditions are often referred to as children with special needs. Parents of children with special needs have been shown to have low levels of optimism and gratitude, which can affect the level of subjective well-being. This research aims to prove the influence of optimism and gratitude on the subjective well-being of parents with special needs children. The present study used a quantitative approach with a survey research type. The research location was in Pidie Regency, Aceh, with a sample size of 132 parents aged 20-55. The sampling technique used was simple random sampling. The instruments used in this research include The Satisfaction of Life Scale (SWLS) and Scale of Positive and Negative Experience (SPANE) with a reliability value of 0.710, the Revised Life Orientation Test (LOT-R) with a reliability value of 0.793, and the Gratitude Questionnaire (Q-6) with a reliability value of 0.761. The results show that optimism and gratitude can simultaneously influence the subjective well-being of parents who have children with special needs (ß=0.087, p=0.000). The practical contribution made by optimism and gratitude to subjective well-being is 97.5%. The study revealed that optimism and gratitude are very influential in increasing the subjective well-being of parents. In conclusion, parents with high subjective well-being tend to show confidence, appreciation, and satisfaction in life, thus positively contributing to parental involvement with children.